GARDEN-PATH SENTENCES: DIFFICALTIES OF INTERPRETATION - V. E. Kagan; Yu. Yu. Shadrina; N. V. Vologzhanin (Russian State Vocational Pedagogical University, 2017)
Introduction. Issues of training interpreters in connection with accelerating the recent processes of globalization are today in the focus of attention of scientists and teachers-practitioners. The main task of the interpreter is to transfer the meaning of foreign, often ambiguous texts adequately. The meaning of the utterance in the original language is made up of several clear characteristics that, if neglected, may cause serious errors in translation. One such characteristic is the syntactic structure of the original message. Unfortunately, linguistic exercises that form and develop the ability of students to solve the translation goals rarely include tasks to teach the correct perception and reproduction of polysemantic (homonymous) messages, which can be translated correctly only under condition of knowing about the syntax of a foreign language.The aim set out in article is the search of possibilities to train professional translators better on the bases of their learning to implement syntactic analysis of the text.Methodology and research methods. The work is based on the competence approach to the training of student translators. The complex of interrelated scientific methods was used, the main of which is the experiment.Results and scientific novelty. The typology of garden-path sentences (statements and messages) is given, the structure of which may cause ambiguity. With the help of quantitative data translation peculiarities of these sentences are characterized. The conducted experiment, where participants were 60 students of theUralStatePedagogicalUniversity (Ekaterinburg) and theInstitute ofInternationalRelations (Ekaterinburg), concluded that the syntactic analysis of garden-path sentences is the problematic point for the translation of texts from English into Russian. Specific examples of exercises for the development of skills of this kind of analysis while studying the course of "Translation Practice" are described. It is noted that parsing as a professional competence of a future translator is formed in the process of training activities and integrated efforts of various departments of anyLanguageSchool/ University.Practical significance. The results of the study can be used by teachers of foreign languages, working both in linguistic and in non-linguistic schools/ universities.